Action of extracts obtained with organic solvents from Minthostachys verticillata(Griseb.) Epling on viability of Herpes simplex Type 1 virus (HSV-1) - Sabini, Maria Carola (2010)
It has demonstrated “in vitro” antimicrobial activity exerted by extracts from Minthostachys verticillata (peperina). Objective: Investigate antiviral action of organic extracts of peperina against Herpes simplex virus. Experimental: Vero cells and Herpes simplex virus type 1 strain KOS were used. Aerial vegetal parts of plant were submitted to sequential extraction with n-hexane, chloroform and methanol for 48 h at room temperature. Extracts n-hexanic (N-HE), chloroformic (CE) and methanolic (ME) were obtained. They were added on cell monolayers, and incubated for 48 h at 37°C. Cell viability was determinated by Neutral Red uptake (NRU) after treatment of cells with different concentrations of extracts (10-1000 μg/ml). The same method was performed to evaluate antiviral action exerted by N-HE (100-250 μg/ml), CE (100-500 μg/ml) and ME (range 80-200 μg/ml). Results and discussion: The three extracts showed dose-dependent cytotoxic activity on Vero cells with CC50 values: 502 μg/ml for CE, 244 μg/ml for N-HE and 192 μg/ml for ME. The replication of Herpes simplex virus type 1 “in vitro” was inhibited by each extract at non cytotoxic concentrations. The extracts showed selectivity of action because all concentrations tested inhibited more than 60% of viral production. The results are promising for future natural therapy antiherpetic.